Implementation of Sustainable Development Goals (SDGs) Through Rumah Rempah Cafe at Universitas Anwar Medika - Farida, Elis Anita; Fitria, Tri Dina; Kusumo, Suryo Hadi (Journal of Development Research, 2024)
Health is one of the targets of sustainable development goals (SDGs). Many are related to the health aspect that determines health itself. Implementation of SDGs in the Indonesian context through traditional herbal medicine innovation development activities. Traditional herbal medicine based on spices is a legacy from generation to generation. This traditional herbal medicine can also be known as a short-term, medium-term, and long-term preventive measure. Although references and applications in society are many normative recommendations about potentially beneficial approaches, evidence regarding the implementation strategy adopted by the Rumah Rempah cafe is still limited. The findings show that the commitment of the Rumah Rempah Cafe at Universitas Anwar Medika is moving forward with research activities so that Rumah Rempah products cauld be scientifically accounted for. The generation that becomes a Rumah Rempah consumer in terms of age is dominated by the Millennial generation (64.1%) and Generation X (21.8%), female gender (74.6%) with a high level of education being the dominant consumer, namely 71.8%. Rumah Rempah Cafe is an alternative to maintaining ancestral heritage, providing positive drinks for the body and according to the tastes of the millennial generation and X-Generation. The consumption of spices as traditional herbal medicine is beneficial for boosting immunity, relieving pain, improving digestion, and detoxifying the body. Rich in antioxidants and anti-inflammatory compounds, herbal spice remedies also help maintain the body's balance and health naturally.